DONGNAI IN PROTOHISTORY: THE MEETING PLACE OF MANY STREAMS OF CULTURES - Lâm Thị Mỹ Dung (Tạp chí Khoa học Đại học Đà Lạt)
Regarding protohistoric and early historic archeology in southern Vietnam, perhaps it is not too exaggerated to consider the Southeast Region as a starting place for the convergence and spread of cultural flows. Traces of the activities of the ancient people here stretched from the Stone Age - Metal Age - Historical Age and are distributed on many different terrains. The factors of “Clement weather - Favorable terrain - Concord among the people” in the Southeast Region have long been cited by multiple researchers to explain the concentration and diversity of archaeological relics here. This study places the Southeast Region - Dongnai in the context of the area in early history (5th century BC to 1st-2nd century AD) to focus on several issues: the context of early history of Vietnam and mainland Southeast Asia,early historicresidential communities in Dongnai, andthe value of archaeological heritage in early history and sustainable development in Dongnai.